CRITICAL ANALYSIS OF STOCK FROM AN OPTIMAL PORTFOLIO PERSPECTIVE: (Case Study of Sharia Banking Companies Listed on the IDX) - Andi Ibbar; Anwar Anwar (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
This study aims to conduct a comprehensive evaluation of the shares of Islamic banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2022, focusing on the optimal portfolio perspective. The method used in this research is a descriptive quantitative approach. The population studied was all Islamic banking companies listed on the IDX during the period mentioned. The sample was selected using purposive sampling technique, with certain criteria to select Islamic banking companies listed on the IDX during the period 2020 to 2022. As a result, three stocks were selected as samples of this study. This study uses a single index model to analyze the data. The results of the analysis showed that of the three stocks sampled, none met the criteria to be included in the optimal portfolio. These stocks are considered not meeting the standards set because the expected return value is smaller than the systematic risk value. Nonetheless, these findings provide valuable insights into the performance of stocks of Islamic banking companies on the IDX during the study period. In addition, it also highlights the importance of conducting periodic portfolio evaluations to identify potential changes in stock performance and optimize the allocation of financial resources. This study makes an important contribution to the understanding of optimal investment strategies in the context of Islamic banking companies in the Indonesian capital market.